الإعجاز العلمي في حديث نقصان عقل المرأة = Scientific miracles in hadith stated that women are deficient in mind - Mohammed Yaqub, Mohammed Abullais Shamsuddin; Abdul Sattar, Aisha Khaleela (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يدور جدل كثير، ولغط شديد حول وضع المرأة في الإسلام، وكثيرًا ما يُتهم الإسلام بأنه ينتقص من حقِّ المرأة في الحياة، والوجود، والفكر. وتُعقد لأجل ذلك الفعاليات، والندوات، والمناظرات في محافل علمية مرموقة. وأكثر ما ينبري له العلماء فيها هو التركيز حول قضية اعتبارها ناقصة عقل؛ مستشهدين في هذا الباب بالحديث الوارد في الصحيحين من أنّ النساء ناقصات عقل ودين. والتساؤل الرئيس المثار هنا أَيصحُّ ما يزعمونه في هذا الصدد من أنَّ المرأة فعلاً ناقصة عقل؟! وأَحقًّا وصفها الرسول  بذلك، وهل كان قاصدًا مَا فُهِمَ من الحديث؟ أمْ أنَّ الأمر على خلاف ذلك؟! وللإجابة عن هذه التساؤلات المثارة، حاول البحث جمع أقوال العلماء في هذا الصدد، وذكر التأويلات التي حامت حول نقصان العقل والدين، وبيان الإعجاز العلمي فيه من خلال العلم الحديث وأقوال علمائه حول عقل المرأة لإثبات صحة هذا الحديث. وقد استخدم البحث منهجين، وهما: المنهج الاستقرائي وذلك لاستقراء الشبهات حول هذا الحديث، والمنهج التحليلي وذلك لنقد تلك الشبهات والرد عليها ردا غير مباشر، وقد توصل البحث إلى أنَّ علماء الحديث أجمعوا على صحة حديث ناقصات العقل، وعلى أنه لا إشكال في مفهومه، حيث إنَّ نقص الدين الوارد في الحديث يمكن أنْ يُقصد به نقص كمال تديّن الإنسان وضعف استقامته، وكذلك وصف النبي  للنساء بأنهن (ناقصات عقل)؛ وصفٌ مُعجِزٌ دقيقٌ جدًّا من الناحية العلِميّة، فقد أثبت علماء التشريح أنَّ هناك نقصانًا في حجم دماغ المرأة، وفي عدد خلاياه، ونقصانًا في حجم قلبها، وذلك مقارنةً بدماغ الرجل وقلبه. ********************************************** There is a great deal of controversy about the status of women in Islam, and Islam is often accused of denying women's rights to life existence, and thought. Pertaining to this issue, may events, seminars and debates are organised in prestigious scientific forums. Many scholars who have delved in this issue argue that women lack focus and, by citing the hadith stated in the As-ØaÍÊÍayn that women are deficient in mind and religion. The issue raised here is either the claim in this regard to women is valid or otherwise. Additionally, this research will also examine whether or not it is true that Prophet (SAW) described women as such. Is it the actual meaning understood from the ×adith or merely an interpretation? To answer these questions, the researchers tried to collect the scholars’ opinions in this regard, and the interpretations that have been made about the lack of reason and religion in women. The researchers found that this view regarding women the matter is agreed upon by Íadith scholars and is not problematic in its concept. This is because, the lack of religion as mentioned in the Íadith means perfection of human condemnation and weak integrity. The Prophet’s (SAW) description of women as lacking in mind is a detailed one. Scientists also have shown that there is a decrease in the size of a women’s brain, number of cells, and the size of her heart, compared to the brain and heart of a man.